The Symbol of Alexander in the Stories of Passhakhoja (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the unique portrayal of Alexander in Poshshakhoja's stories. The article advances the theoretical idea that Pashshakhoja, through the character of Alexander, illuminates the socio-political situation.